Educational Revolution in The Digital Era: Integrating Technology in The Independent Curriculum - Chudzaifah, Ibnu; Nailil Hikmah, Afroh (Journal of Quality Assurance in Islamic Education (JQAIE), 2024)
Technology, including education, has become an integral part of life in this digital era. Technological developments bring new challenges and opportunities that change the traditional learning paradigm. The concept of Independent Learning in Indonesia, which focuses on student participation and autonomy, is increasingly relevant with technology support. This research uses qualitative methods that focus on literature reviews. Information was collected by analyzing articles, journals, and books discussing the use of technology in the Independent Curriculum. Research shows that the use of technology in education has a significant impact on student achievement, skills, and engagement. The integration of technology in the Independent Curriculum not only enriches learning content but also supports the achievement of the Pancasila Student profile. However, challenges such as gaps in technology access and teacher training must be addressed. With the right approach, technology can be a powerful tool for improving the quality of education and preparing students for an increasingly digital future.